Figure replication in Soeharto Visual Meme - rizky noviasri; Yasraf Amir Piliang; Riama Maslan Sihombing (Fakultas Seni Rupa dan Desain ITB, 2016)
Internet meme vernacularly known as funny pictures with caption. One of them picture of Soeharto icon, smiling and waving his hand, said